Comparable Efficacy of Terbinafine and Itraconazole in the Treatment of Tinea Pedis - Wahab, Md Abdul; Uddin, Mohammad Jamal; Hassan, Biswas Shahen; Islam, Md Zafrul; Bhuiyan, Ishrat; Siddique, Mohammad Rahmat Ullah (Bangladesh Journal of Medicine, 2013)
Background: Tinea pedis (athlets foot) is the most common fungal infection. Relapse is common in tinea pedis and may be result of recurrence following inadequate treatment or reinfection. Objective: To evaluate the comparable efficacy of terbinafine and itraconazole in the treatment of tinea pedis. Methods: 120 patients of tinea pedis confirmed by KOH microscopy were included in the study. The study was carried out in three different Hospitals and Private Chambers for a period of 3 years from July 2006 to June 2009. Mean age of the patients was 40.28±10.23. The patients were devided into 2 equal group:A & B. Group- A was given terbinafine 250 mg/day and group-B was given intraconazole 200 mg/day for 2 weeks. Results: Follow up 2 weeks after cessation of therapy revealed clinical and mycological cure of 93.3% in terbinafine group and 86.6% in itraconazole group. Conclusion: Efficacy analysis revealed that terbinafine is superior than itraconazole in the treatment of tinea pedis (P value 0.224). DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13615 Bangladesh J Medicine 2010; 21: 74-79